ACUTE TONSILLOPHARYNGITIS. RATIONAL PHARMACOTHERAPY - D. V. Kharina; D.Sh. Macharadze (Вопросы современной педиатрии, 2013)
The authors analyzed etiological factors and special issues of diagnostics of inflammatory diseases of the pharynx associated with pain in children. According to etiological factors tonsillopharyngitis can be divided into two main forms: bacterial and viral. The prevalence of viral tonsillopharyngitis is respectively high and, in contrast to bacterial form, this one does not demand systemic antibacterial treatment. The article contains information on the main medicines used for topical treatment of viral inflammation of the pharynx: saline solutions and antiseptic agents. The most appropriate topical antiseptic drug for children with tonsillopharyngitis is combined ones with amylmetacresol and dichlorobenzyl alcohol, not lidocain-containing or nonsteroidal anti-inflammatory ones. The high analgesic effect of such combination is shown in various studies. Moreover, it was found, that hexylresorcinol and amylmetacresol inhibit sodium channels 10-20 times more intensely than lidocain. Significant analgesic effect of amylmetacresol/dichlorobenzyl alcohol is observed in 5 minutes after administration and its duration is 2 hours. Decrease of virulence of influenza A, respiratory syncytial and coronaviruses under exposure to amylmetacresol and dichlorobenzyl alcohol was also proved. Availability of several medicinal forms and its high pharmacological safety make this drug the most optimal for treatment of pain syndrome in tonsillopharyngitis in children.